PENERAPAN METODE PEMBELAJARAN JOYFUL LEARNING UNTUK MENINGKATKAN HASIL BELAJAR DI SMPN 37 MAKASSAR - Nabila, Zaki; Mustamin; Nengsih, Ratika; Wahab, Abdul; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the implementation of the joyful learning method in improving students’ learning outcomes in Islamic Religious Education (PAI) in class VIII.F at UPT SMP Negeri 37 Makassar. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 34 students. Data were collected through observation, learning outcome tests, and documentation. The results showed that in the pre-action stage, only 12 students (35%) achieved the Minimum Mastery Criteria (KKM) with an average score of 76. After implementing joyful learning in cycle I, the number of students who achieved mastery increased to 20 students (58%) with an average score of 82. In cycle II, a more significant improvement occurred, with 30 students (88%) achieving mastery and the class average score increasing to 88. In addition to improving learning outcomes, the implementation of joyful learning created a more active, interactive, and enjoyable classroom atmosphere, enhancing students’ motivation and confidence. Therefore, the joyful learning method proved to be effective in improving students’ learning outcomes in Islamic Religious Education.